The use of echocardiography as a health assessment tool in green sea turtles (Chelonia mydas). Issue 1 (23rd November 2020) - March, DT; Marshall, K; Swan, G; Gerlach, T; Smith, H; Blyde, D; Ariel, E; Christidis, L; Kelaher, BP
Abstract : There are limited techniques available to assess the health of sea turtles as physical examination has little correlation to clinical findings, and blood reference intervals are broad and provide limited prognostic significance. Advances in the portability of ultrasound machines allow echocardiography to be increasingly used in the health assessments of wild animals. This study performed blood analysis and echocardiograms on 11 green sea turtles upon admission to a rehabilitation clinic and six animals before release. Significant differences were seen between groups, with admission animals having significantly smaller diameters of the cavum arteriosum at systole and diastole, smaller E‐waves and an increased fractional shortening. Pre‐release animals displayed significant increases in the maximum blood velocities of both the pulmonary artery and the left aorta. Significant negative correlations were seen between fractional shortening and uric acid and between the velocity time integral of the pulmonary artery and urea. The pulmonary artery velocity time integral was also significantly correlated to the E wave. Furthermore, there was asynchrony between the cavum arteriosum and the cavum pulmonale and the detection of a parasitic granuloma in the ventricular outflow tract of one animal. Overall, the results suggest that cardiac function in stranded green sea turtles is significantly impaired and that echocardiography has applications in the health assessments of green sea turtles.